Thermal conductivity determination of suspended mono- and bilayer WS2 by Raman spectroscopy - Peimyoo, Namphung; Shang, Jingzhi; Yang, Weihuang; Wang, Yanlong; Cong, Chunxiao; Yu, Ting (Nano research, 2015)
We report the thermal conductivities of monolayer （1L） and bilayer （2L） WS2 grown by chemical vapor deposition （CVD）, which are determined by use of temperature and excitation dependences of E2g^1 and A1g Raman modes. The first-order temperature coefficients of E2g^1 and Alg modes in both supported and suspended WS2 layers were extracted. The frequency shift of the A3g mode with temperature is larger than that of the E1 mode for 1L-WS2, which is 2g attributed to stronger electron-phonon coupling for the A1g mode than that for the E12g mode. Moreover, by use of the shift of the phonon mode induced by laser heating, the thermal conductivities at room temperature were estimated to be 32 and 53 W/（m.K） for 1L- and 2L-WS2, respectively. Our results provide fundamental information about the thermal properties of WS2 layers, which is crucial for developing applications of atomically-thin WS2 devices.